Tailoring the Mechanical Properties of 3D Microstructures Using Visible Light Post‐Manufacturing. Issue 30 (3rd June 2019) - Gernhardt, Marvin; Blasco, Eva; Hippler, Marc; Blinco, James; Bastmeyer, Martin; Wegener, Martin; Frisch, Hendrik; Barner‐Kowollik, Christopher
Abstract: The photochemistry of anthracene, a new class of photoresist for direct laser writing, is used to enable visible‐light‐gated control over the mechanical properties of 3D microstructures post‐manufacturing. The mechanical and viscoelastic properties (hardness, complex elastic modulus, and loss factor) of the microstructures are measured over the course of irradiation via dynamic mechanical analysis on the nanoscale. Irradiation of the microstructures leads to a strong hardening and stiffening effect due to the generation of additional crosslinks through the photodimerization of the anthracene functionalities. A relationship between the loss of fluorescence—a consequence of the photodimerization—and changes in the mechanical properties is established. The fluorescence thus serves as a proxy read‐out for the mechanical properties. These photoresponsive microstructures can potentially be used as "mechanical blank slates": their mechanical properties can be readily adjusted using visible light to serve the demands of different applications and read out using their fluorescence. Abstract : A new class of photoresist‐containing anthracene functionalities for direct laser writing is realized, enabling visible‐light‐gated control over the mechanical properties of 3D microstructures post‐manufacturing. Upon irradiation, additional crosslinks are formed and fluorescence is lost at the same time. Reading out the fluorescence of the microstructures can thus serve as a simple, noninvasive proxy for the determination of the mechanical properties.